Acute-on-Chronic Liver Failure: The Role of Precipitating Illness - Solà, Elsa; Fernandez, Javier; Ginès, Pere (Seminars in Liver Disease, 2016)
Acute-on-chronic liver failure (ACLF) is a complex syndrome that develops in patients with cirrhosis at any stage during the natural history of the disease. In most cases, the development of ACLF is associated with an identifiable precipitating factor. Overall, the most common precipitating events are bacterial infections. Although data suggest that any type of infection may trigger ACLF, spontaneous bacterial peritonitis, secondary peritonitis, and pneumonia appear to be the most common types of infection leading to ACLF. Nevertheless, frequency and characteristics of precipitating factors differ among geographical areas. Although in the West the most common precipitating factors are bacterial infections followed by active alcoholism, in the East the most common triggering events are exacerbation of hepatitis B virus followed by bacterial infections. Although precipitating events may be crucial in the development of ACLF, mortality appears to be independent of the type of precipitating factor. Finally, it should be noted that in up to 20 to 40% of patients with ACLF no precipitating factor can be identified. It is suggested that in these patients, bacterial products derived from bacterial translocation or damage-associated molecular patterns resulting from injured liver tissue cells may act as triggering factors.
Keywords: acute-on-chronic liver failure; precipitating factors; bacterial infections; cirrhosis; hepatitis B virus